Agricultural Credit Mobilisation and Food Security in Nigeria: Investigating the Interaction Effect of Urbanisation - Ajiboye, Wale Thomas Ajiboye; Otayokhe, Esther Yemi Otayokhe; Ibitoye, Olusola Anthony Ibitoye; Jimba, Kareem Isiaka Jimba; Ogundele, Biodun Thomas Ogundele; Lawal, Usman Olarewaju Lawal; Oguntuase, Oluwakemi Margaret Oguntuase (African Journal of Stability and Development (AJSD), 2025)
Nigeria’s escalating food insecurity crisis is inadequately addressed by existing research, which often relies on qualitative insights and limited household surveys, failing to capture critical dimensions of the issue. Conventional food security metrics lack comprehensiveness, emphasising the need for broader approaches. This study fills the gap by employing holistic food security indices to offer a multidimensional evaluation and investigate urbanisation’s moderating role in the relationship between agricultural credit mobilisation and food security. Using 24 years of data (2000–2023) from the Central Bank of Nigeria (CBN) statistical bulletin and the Food and Agricultural Organisation (FAO) database, the study employs advanced econometric methods, including autoregressive distributed lag (ARDL) estimation, unit root testing, F-bound tests for cointegration, and principal component analysis (PCA). Results show that agricultural credit mobilisation exerts a significant negative impact on food security, while urbanisation amplifies this negative impact, further intensifying the nation’s food insecurity challenges. Hence, the study recommends tailored agricultural credit schemes that address the specific needs of rural and urban areas. Policymakers should prioritise sustainable agricultural practices and food production systems that align with Nigeria’s broader goals for resilience and sustainable development.